The translational content and expression of intracellular sensors under endoplasmic re-ticulum stress in diabetic rats - Klys, Y. G.; Natrus, L. V.; Kerimov, T. R.; Smirnov, S. M. (Regulatory Mechanisms in Biosystems, 2024)
Endoplasmic reticulum stress (ER stress) activates the unfolded protein response (UPR) as a defense mechanism for maintaining cellular vital activity. Data on interaction between pathways of UPR-sensors, their role and participation in the recovery of regulatory proteins at constant level are currently being accumulated. An experimental model of type 2 diabetes mellitus (T2DM) was reproduced in male rats fed on 3-month high-fat diet with additional streptozotocin administration. Rats in different groups were treated with metformin, propionate, and their combination for 2 weeks. We analyzed the expression of the GRP78, PERK, IRE-1, and ATF6 genes in gastric glandulocytes using PCR primers. The quantitation of protein content of the GRP78, PERK, IRE-1, and ATF6 genes was performed using western blotting. Statistical intergroup differences were calculated using a one-way ANOVA test followed by Tukey’s post-hoc. Comparison of mRNA and protein contents at rest state, in condition of ER stress and drug treatment, as well as the study of correlations between UPR-sensors, provides a basis for the development of the concept of defense mechanism activation in gastric glandulocytes under T2DM conditions. Under stress, chaperone GRP78 plays a crucial role to prevent protein misfolding: it dissociates from ER, enters cisternae and inactivates misfolded proteins. The ATF6 pathway is activated in all conditions. It probably activates transcription of the corresponding content turnover sites in both GRP78 and ATF6. The IRE-1 and PERK pathways are activated in glandulocytes under different circumstances, and they probably target to different regulatory actions. Combination drug treatment in T2DM conditions induces activation of all signaling sensors in the UPR system with simultaneous maximal downregulation of GRP78, causing a balance in the intracellular homeostasis system.